2021
DOI: 10.1017/pds.2021.22
|View full text |Cite
|
Sign up to set email alerts
|

A Robust Design Research Landscape - Review on the Importance of Design Research for Achieving Product Robustness

Abstract: The strive for design principles, qualitative and quantitative design tools, and product development methodologies that enable and support the design of robust products, that is products which are insensitive to noise and variation, is an ongoing challenge for both practitioners and academics. This paper reviews and classifies recent research efforts dedicated to robust design originating from the design society and carves out important challenges and potentials for future research. The main novelty of the pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…In addition, it has not yet been thoroughly resolved how robustness in the design domain can be defined in the model presented and how it can be integrated into the robustness evaluation. Furthermore, the combined approach has to be integrated into the product development process in a clear and consistent way, which according to EIFLER AND SCHLEICH [18] is rarely done in research in the field of robust design and leads to unclear necessity of approaches. They [18] also show that the use of approaches is rarely investigated, therefore the present approach of this paper has to be evaluated in the future through a user study and the benefit has to be quantified.…”
Section: Evaluation Of the Model Combination And Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, it has not yet been thoroughly resolved how robustness in the design domain can be defined in the model presented and how it can be integrated into the robustness evaluation. Furthermore, the combined approach has to be integrated into the product development process in a clear and consistent way, which according to EIFLER AND SCHLEICH [18] is rarely done in research in the field of robust design and leads to unclear necessity of approaches. They [18] also show that the use of approaches is rarely investigated, therefore the present approach of this paper has to be evaluated in the future through a user study and the benefit has to be quantified.…”
Section: Evaluation Of the Model Combination And Discussion Of Resultsmentioning
confidence: 99%
“…However, many approaches from the tolerance domain require quantitative information and are therefore only applicable in the later stages of the development process. There are qualitative approaches in the tolerance domain [18], which for example focus on linking geometry, function, and requirement [19]. Moreover, there are research activities exploring abstracted structures to link this information for the tolerance domain [20,21].…”
Section: Related Workmentioning
confidence: 99%
“…Different industrial sectors are represented in the Robust Design SIG, so that in addition to Precision Engineering – the main focus in Ilmenau – challenges and approaches from production engineering, automotive and aerospace industries, medical and drug delivery devices and many others are addressed (Eifler et al 2023). In research, questions concerning all steps of the development process are discussed, in order to develop robust solutions in the context of the different requirements and external as well as internal influences (Eifler & Schleich 2021; Husung et al 2023; Li et al 2023). Increasingly, approaches from Virtual Product Development are being used: from tolerance simulations (Heling et al 2018) to Pareto optimisations (Bode et al 2023) and knowledge-based solutions (Faheem et al 2023; Walsh et al 2023).…”
Section: Design Science In Ilmenaumentioning
confidence: 99%
“…Since all of these domains have their own terminology and understanding, and employ different approaches and tools to address variation and/or robustness in design and real time operation, a more systematic and holistic approach is necessary to carefully align all perspectives across different design phases. A recent review of RD-related publications within the design community (Eifler and Schleich, 2021) has unveiled a largely unstructured research field. Based on a mapping of publications at ICED and Design conferences (in the period from 2011 to 2021), it was shown that the design research perspective on product robustness lacks a consistent terminology and does not provide a systematic view on multidisciplinary product development, with few systematic efforts to show method validation or insights on the actual method implementation and impact in an industry context (e.g., Campean et al, 2022).…”
Section: Introductionmentioning
confidence: 99%